The Covariation of Sexual Fantasies and Behaviors Among Self-Identified Sexually Aggressive Criminal and Noncriminal Samples. (April 2022) - Ronis, Scott T.; Knight, Raymond A.; Vander Molen, Lauryn
This study examined the association of sexually appetitive fantasies and sexually coercive behaviors among adult men convicted of nonsexual crimes ( n = 159) and adult men with no criminal histories ( n = 219). Individuals completed the Multidimensional Assessment of Sex and Aggression (MASA) and, on the basis of these reports, were classified whether or not they had ever attempted to assault or coerce someone sexually. Consistent with fewer opportunities to engage in sexual behavior, individuals with criminal histories reported generally less preoccupation, compulsivity, and frequency than did noncriminal individuals. Regardless of criminal history, self-identified sexually coercive men reported significantly more sexually appetitive fantasy and behavior in general and sexually deviant behavior in particular than did noncoercive males. Implications of these findings for research, theory, and dispositional decisions are discussed.